Pattern of Inheritance Distribution of Gono Gini's Assets Among Residents of Bandar Lampung City - Zaelani, Abdul Qodir; Hilal, Syamsul; Hanif, Abdul (al-'adalah, 2021)
This study explores the pattern of determining/distributing the inheritance of Gono Gini assets among the citizens of the city of Bandar Lampung. The aim is to reveal what factors contribute to the emergence of the different patterns in determining and distributing inheritance among the community members. This research is empirical, using a qualitative analysis approach. The data were obtained through observations and interviews with some religious and community leaders in the city whom were selected based on the purposive sampling technique. This study finds out the fact that the diversity of determining/distributing patterns of gono gini assets among residents of the city of Bandar Lampung is mainly influenced by, among other things, the heterogeneity of the population consisting of various ethnicities, cultural backgrounds, traditions, habits, and tendencies in understandings cultural norms, law and religion.